2012
DOI: 10.1097/mcg.0b013e31824f1af4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bisphosphonates on Bone Mineral Density and Fracture Prevention in Gastric Cancer Patients After Gastrectomy

Abstract: Therapy using bisphosphonates might be effective at increasing BMD and reducing fracture risk in gastric cancer patients after gastrectomy. Further well-designed randomized controlled trials are needed for confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Biphosphonates together with calcium and vitamin D are also very important in preventing osteoporosis and lowering the fracture rates. They have been shown to be effective in preventing skelatal related adverse events and should be considered in these patients [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biphosphonates together with calcium and vitamin D are also very important in preventing osteoporosis and lowering the fracture rates. They have been shown to be effective in preventing skelatal related adverse events and should be considered in these patients [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the incidence of postgastrectomy metabolic bone disorder varied widely due to the lack of established methods for evaluating osteoporosis. With the development of a useful method for evaluating osteoporosis (DXA) and effective agents for treatment (bisphosphonates), and also because the prevalence of osteoporosis is high after gastrectomy, bisphosphonates have been commonly administered to patients receiving gastrectomy prophylactically and therapeutically [10,22] . A previous study showed that risk factors for osteoporosis in patients undergoing gastrectomy were female gender and age >70 years, but not the type of gastrectomy (partial vs. total) or number of years after operation (<20 vs. ≥ 20 years) [23] .…”
Section: Discussionmentioning
confidence: 99%
“…In a small study of 47 post-gastrectomy patients, oral bisphosphonate treatment with alendronate or risedronate significantly reduced incident fractures and increased BMD at both the lumbar spine and femoral neck compared to no treatment (P<0.05 for all comparisons). (73)…”
Section: Other Malignanciesmentioning
confidence: 99%